WHAT IS THE TRUE HAPPINESS? (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Typically, we cannot always show happiness what we can feel something or not. It is just indicated in our lifestyle - how we communicate with friends, relatives or parents and children, or where we live peacefully, the ways how we can meet our needs, in monthly how much money we can earn or something like that. As a whole, in what way we are living or how we are building a desired life what we dreamt of being happy person in the past. Happiness is a subjective and multifaceted emotion that encompasses feelings of joy, contentment, and fulfillment. It is a state of well-being and satisfaction with one's life, where individuals experience a sense of purpose, meaning, and positive emotions. Happiness can vary from person to person, as it is influenced by individual values, beliefs, and life circumstances. It is not solely dependent on external factors such as material possessions or achievements but is often found within oneself through self-awareness, acceptance, gratitude, and meaningful connections with others. "So really, it’s not that happiness isn’t a virtuous thing to which you should aspire, or that happiness isn’t something you’re ever allowed to feel. The reality is that inner peace is the true happiness, and everything else is just a false means of trying to convince yourself that you are “okay.”"[1]